Anthocyanins as functional food components - R. S. Yudina; E. I. Gordeeva; O. Yu. Shoeva; M. A. Tikhonova; E. K. Khlestkina (Вавиловский журнал генетики и селекции)
Among the natural pigments, anthocyanins are assumed to represent one of the most studied groups. Starting with the first studies on the physicochemical properties of anthocyanins carried out in the 17th century by British naturalist Robert Boyle, the science about these unique compounds has progressed substantially. To date, the structure and functions of anthocyanins in plant cells have been well studied, and the pathway of their biosynthesis is one of the most fully characterized pathways of secondary metabolite biosynthesis at both the biochemical and genetic levels. Along with these fundamental achievements, we are beginning to realize the potential of anthocyanins as compounds of industrial importance, as pigments themselves, as well as components of functional food that contribute to the prevention and reduction of risk of chronic diseases. For a long time, the biological activity of anthocyanins has been underestimated, in particular, due to the data on their low bioavailability. However, studies showed that in humans and animals, these compounds are actively metabolized and the bioavailability, estimated taking into account their metabolites, exceeded 12 %. It has been experimentally shown that anthocyanins have antioxidant, anti-inflammatory, hypoglycemic, antimutagenic, antidiabetic, anti-cancer, neuroprotective properties, and they are beneficial for eye health. However, the studies conducted cannot always explain the molecular mechanism of action of anthocyanins in the human body. According to some reports, the observed effects are not due to the action of anthocyanins themselves, but to their metabolites, which can be more biologically active because of their increased bioavailability. Other data ascribe the positive effect on human health not to individual anthocyanins, but to the whole complex of polyphenolic compounds consumed. The review summarizes the results of the studies of anthocyanins as components of functional food. Special attention is paid to genetic control of the pigment synthesis. These data are of particular importance in respect to the initiated breeding programs aimed at increasing the content of anthocyanins in cultural plants.